EPIDEMIOLOGY OF SYMPTOMATIC EPILEPSIES IN SMOLENSK REGION - N. N. Maslova; N. V. Yurieva (Эпилепсия и пароксизмальные состояния)
Abstract: symptomatic epilepsy remains a difficult problem for the diagnosis and effective treatment. The main epidemiological indicators of symptomatic epilepsies, methods of diagnosis and semiotics attacks, aspects of the therapy probe and combined treatment with primenenie months were studied.